The Global Challenge of Internal Displacement - Francis Mading Deng (Washington University Journal of Law & Policy, 2001)
I would like to address the subject of internal displacement from the perspective of four issues: the magnitude of the crisis, my conceptual approach to the mandate, the scope of activities I have undertaken pursuant to the mandate, and the need to address the root causes of internal displacement.
Keywords: Internally displaced persons; Human rights; United Nations. Commission on Human Rights; Refugees; Internal migration